Defence Reform and Military Modernization in the Philippines in the perspective of the South China Sea Conflict - Klemensits, Péter (Overcoming Controversies in East Asia, 2017)
By the end of the 20th century, the Philippine military became one of the weakest armed forces in Southeast Asia. For the past five decades, the Philippine military has had to fight and contain communist insurgents and Islamist groups alike, and thus the army has long been focussed on internal defence. However, after several incidents with China in the South China Sea, the presidency of Benigno S. Aquino III brought about significant changes, and serious steps have been taken to reform the defence establishment and upgrade the military.The author examines the main aspects of the defence reforms then the politicalmilitary aims of the government in the context of the South China Sea conflict. In conclusion, the article argues that the change of the international and domestic security environment compels the cabinet to try to upgrade the armed forces capabilities and achieve a minimum credible defence posture. The process however required careful balancing from the cabinet between the strategic directions and development options, not forgetting the financial constraints and the political factors as well.